Generalized escape paths for dynamical tunneling in QFT - Darmé, Luc; Jaeckel, Joerg; Lewicki, Marek (Physical review, 2019)
We present a formalism based on the functional Schrödinger equation to analyze time-dependent tunneling in quantum field theory at the semiclassical level. The full problem is reduced step by step to a finite dimensional quantum mechanical setup and solved using the Wentzel-Kramers-Brillouin approximation. As an example, we consider tunneling from a homogeneous oscillating initial state in scalar quantum field theory.